Mother’s Education and Antenatal Care Visits in Nepal - Shrestha, Bidhya (Tribhuvan University Journal, 2018)
The proper use of antenatal care (ANC) visit is the first step to prevent both mother and child health. This is also one of the key components to achieve the Sustainable Development Goals by 2030. The study is an attempt to assess the relation between mother’s education and utilization of ANC services in Nepal. It is completely based on data of national representative 2016 Nepal Demographic and Health Survey that covered 2,746 currently married women, aged 15-49 years who had at least one child in the last three years preceding the survey. Logistic regression was used to analyze the effect of education on the utilization of ANC services. Results showed that a higher level of maternal education increased the chance of utilizing ANC services than those with little or no education. The importance of maternal education continued even when other socioeconomic factors are taken into account. This indicates that mother’s education contribute to increase the use of proper ANC services.